Invarianza Factorial del Cuestionario de Autoconcepto Dimensional AUDIM-M en Hombres y Mujeres Universitarios Mexicanos - Domínguez, Héctor Franco; Vega, Humberto Blanco; García, Perla Jannet Jurado; Vásquez, Susana Ivonne Aguirre; Ornelas, José René Blanco (European Scientific Journal, ESJ, 2018)
The present study analyzes the psychometric properties of the Dimensional Self-Concept Questionnaire (AUDIM-M) in university men and women. The total sample was of 730 participants; 365 women and 365 men, with a means age of 20.55 years (SD = 1.87) and 20.78 years (SD = 1.90) respectively. According to the established psychometric requirements, the confirmatory factor analyzes showed that a four-factor structure (personal selfconcept, physical self-concept, social self-concept and academic self-concept) is viable and suitable for both populations (women and men). In addition, the factorial structure, the factorial loads and the intercepts are considered invariant in the two populations; however, there are differences between the populations for the means of the factors physical self-concept and social selfconcept.